Pengaruh Akuntabilitas Publik dan Transparansi Laporan Keuangan Terhadap Kepercayaan Donatur pada Yayasan PPPA Daarul Qur’an Nusantara - Athifah Athifah; Ai Nur Bayinah; Efri Syamsul Bahri (Universitas Muhammadiyah Sidoarjo, 2018)
Non-profit organizations as the institute for public sector own functions and usefulness of providing facilities to the public by using wealth awarded by benefactors or society. But these functions cannot take place in good if rules out the importance of public management system. Among them is application of public accountability and transparency, especially for financial statements. Transparency indicates accountability form addressed to the foundation’s donors. Donors can be relied upon that trust and activities in organization can run continuously. These characteristics make the non-profit organization can not release itself from interests community area. This study will test related to the influence of public accountability and transparency from financial statements toward donors in PPPA Daarul Qur’an Nusantara Foundation. This test is quantitative research with multiple regression statistical analysis. The statistical result shows that at the same time (simultaneously), public accountability and transparency financial statements have a positive effect towarddonors trust. However, in partial or separate variable, public accountability does not have an influence toward trust of Donors. While the transparency of financial statement has influenced significantly.